Evaluation of asphalt pavement layer bonding stress - Du, Jia-Chong (Journal of Civil Engineering and Management, 2015)
This study is to evaluate the bonding shear stress between asphalt pavement layered structures with emulsion and cutback asphalt as tack coat materials. A simple direct shear test device is set up for testing the shear force of the pavement composite interface. The test results show that the shear force decreases with an increase in temperature. It had a maximum value at optimum application rate and the emulsion asphalt used exhibited higher shear force than that of cutback asphalt. The shear stress model represented by exponential equations between shear stress and temperature is reasonable and is not significantly different to the shear stress from experimental field test, in accordance with the statistic of analysis of variance test. The shear stress modeling developed in this paper provides a valuable method to simulate the shear stress of a different nominal aggregate gradation and tack coat material.